PENGGUNAAN BAHAN AJAR DALAM BENTUK BUKU SAKU UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA POKOK BAHASAN ASAM BASA DI KELAS XI MIA SMA NEGERI 2 PEKANBARU - Gita M.S, Rentha; Herdini, Herdini; Erviyenni, Erviyenni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aimed to increase students results implementation of the use of teaching materials in the form of pocket books on subject acid base in XI MIA SMAN 2 Pekanbaru. Instrument in this research is a question of acid base compounds that has been test validation and reliability. Results showed instrument is valid and reliable. The type of this research is experimental research with randomized control group pretest-posttest design. Subject of this research are XI MIA 1 as the experimental class, XI MIA 2 as the control class which were determined randomly after conducting normality and homogeneity test. The experimental group was treated with implementation of the use of teaching materials in the form of pocket books while the control group without implementation of the use of teaching materials in the form of pocket books. The data analysis to test the hypothesis was using t-test right side. Based on the data analysis, it is obtaine tcount = 1,92 and ttable = 1,67 with α = 0,05, dk = 70, tcount > ttable is 3,07 > 1,67, It’s mean implementation of the use of teaching materials in the form of pocket books can improve students results on the subject acid base in XI MIPA SMA Negeri 2 Pekanbaru.Key Words: Acid Basa, Pocket Book, Results Learning